The Anesthesiologists’ Perception of Malignant Hyperthermia and Availability of Dantrolene in China: A Cross-Sectional Survey - Wang J; Yu Y; Gao Y; Wan T; Cong Z; Li Z; Zhou Y; Wang X; Feng L; Han Y; Zhang J; Qu Y; et al. (Dove Medical Press, 2024)
Jiechu Wang,1- 3,* Yao Yu,1,* Ya Gao,1- 3,* Tingting Wan,1- 3 Zhukai Cong,1- 3 Zhengqian Li,1- 3 Yang Zhou,1- 3 Xiaoxiao Wang,4 Luyang Feng,1- 3 Yongzheng Han,1- 3 Jing Zhang,1- 3 Yinyin Qu,1- 3 Xiangyang Guo1- 3 1Department of Anesthesiology, Peking University Third Hospital, Beijing, 100191, People's Republic of China; 2Beijing Center of Quality Control and Improvement on Clinical Anesthesia, Peking University Third Hospital, Beijing, 100191, People's Republic of China; 3Anesthesia and Perioperative Medicine Branch of China International Exchange and Promotive Association for Medical and Health Care (CPAM), Beijing, 100191, People's Republic of China; 4Research Center for Clinical Epidemiology, Peking University Third Hospital, Beijing, 100191, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiangyang Guo; Yinyin Qu, Department of Anesthesiology, Peking University Third Hospital, North Garden Road 49, Haidian District, Beijing, 100191, People's Republic of China, Email puthmzk@hsc.pku.edu.cn; quyinyin@bjmu.edu.cnBackground: Malignant hyperthermia (MH) is a hypermetabolic syndrome with high mortality rates. Early detection and prompt intravenous administration of dantrolene are crucial for effective management of MH. However, there is currently a lack of comprehensive nationwide surveys on the availability of dantrolene and anesthesiologists' understanding of MH in China.Methods: A nationwide survey was conducted between January 2022 and June 2022. Online questionnaires on the cognition of MH among anesthesiologists in China were sent through social platforms to anesthesiologists in mainland China. Data regarding participants' perception of MH-related knowledge, availability of domestic dantrolene, and reported MH cases were collected in this study.Results: Responses were collected from a total of 11,354 anesthesiologists representing 31 provinces across the Chinese mainland. Among the 11 scoring questions, the highest accuracy rates were observed for the question regarding therapeutic drugs for MH (99.3%) and the characteristics of MH (98.0%). Conversely, the question pertaining to the earliest clinical signs of MH had the lowest accuracy rate (23.5%). Significant variations were observed in the scores among different professional titles (P=0.003), academic degree (P< 0.001), hospital classification (P< 0.001), and urban hierarchy (P< 0.001). Of the respondents, 919 (8.1%) anesthesiologists reported dantrolene availability in their hospitals, and 631 (5.6%) indicated unclear. A total of 136 hospitals in this survey reported at least one previous case of MH.Conclusion: Mainland China faces challenges such as insufficient experience in diagnosing and treating MH, as well as difficulty in obtaining dantrolene. To improve the public awareness of MH, it is imperative to establish and promote a refined MH training system. Additionally, a streamlined and rapid dantrolene linkage emergency system should be implemented to ensure prompt access to the drug.Keywords: malignant hyperthermia, dantrolene, China, anesthesiologists, survey